2022
DOI: 10.1371/journal.ppat.1010307
|View full text |Cite
|
Sign up to set email alerts
|

High-level carbapenem tolerance requires antibiotic-induced outer membrane modifications

Abstract: Antibiotic tolerance is an understudied potential contributor to antibiotic treatment failure and the emergence of multidrug-resistant bacteria. The molecular mechanisms governing tolerance remain poorly understood. A prominent type of β-lactam tolerance relies on the formation of cell wall-deficient spheroplasts, which maintain structural integrity via their outer membrane (OM), an asymmetric lipid bilayer consisting of phospholipids on the inner leaflet and a lipid-linked polysaccharide (lipopolysaccharide, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…The acquisition of drug resistance occurs at the cost of reducing capsular polysaccharides and virulence. Murtha et al [ 33 ] studied Enterobacterales and found that meropenem could induce PhoPQ and increase modifications of L-Ara4N. Exposure to different antibiotics can lead to changes in bacterial tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of drug resistance occurs at the cost of reducing capsular polysaccharides and virulence. Murtha et al [ 33 ] studied Enterobacterales and found that meropenem could induce PhoPQ and increase modifications of L-Ara4N. Exposure to different antibiotics can lead to changes in bacterial tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that Vibrio cholerae ( 17 , 18 ), Pseudomonas aeruginosa ( 19 ), and pathogens of the Enterobacterales order ( 21 , 22 ) form viable, nondividing spheroplasts when exposed to lethal concentrations of β-lactam antibiotics over several hours. Importantly, spheroplasts revert to normal rod-shaped growth when the antibiotic concentration is sufficiently reduced ( 21 ), demonstrating a short-term survival mechanism that directly contributes to antibiotic treatment failure.…”
Section: Resultsmentioning
confidence: 99%
“…While we showed that several tolerance factors are transcriptionally regulated, we do not know which transcriptional regulators control these responses. A previous study found that PhoPQ-dependent outer membrane modifications promoted survival in cell wall-deficient spheroplasts ( 22 ), presumably by fortifying the outer membrane to counter large loads of turgor pressure typically absorbed by the cell wall. Specifically, PhoPQ was activated in response to meropenem treatment.…”
Section: Discussionmentioning
confidence: 99%
“…baumannii upregulated genes that fortified the OM and induced autolysins that may act to remodel the cell envelope [110]. In Enterobacter cloacae , the two-component system PhoPQ was found to be necessary for survival of meropenem-induced CWD cells over 24 h [111]. Further analysis of genes controlled by the PhoPQ regulon identified arnT , which encodes a transferase that adds aminoarabinose to lipid A in the OM [111].…”
Section: Requirements For Survival As a Cwd Variantmentioning
confidence: 99%
“…In Enterobacter cloacae , the two-component system PhoPQ was found to be necessary for survival of meropenem-induced CWD cells over 24 h [111]. Further analysis of genes controlled by the PhoPQ regulon identified arnT , which encodes a transferase that adds aminoarabinose to lipid A in the OM [111]. This modification likely increases the OM stability and resilience to mechanical and osmotic pressure.…”
Section: Requirements For Survival As a Cwd Variantmentioning
confidence: 99%